TECHNIQUES OF INTERSECTION – METRICS AS CONNECTORS AND SEPARATORS IN TWITTER RESEARCH - Gerlitz, Carolin; Rieder, Bernhard (AoIR Selected Papers of Internet Research, 2014)
Social media platforms are characterized by the sheer volume of activity and thus data, whilst at the same time only offering very specific and often limited access possibilities. When studying Facebook or Twitter, questions and techniques of delimitation, i.e. the selection of subsets and the use of specific metrics, are particularly relevant. This paper sets out to reflect on metrics in Twitter research as specific techniques that allow to investigate the making of boundaries and connections, while at the same time functioning both as connectors and separators. The question of cutting and slicing has been discussed in relation to sampling techniques in the context of social science research (Uprichard; Bryman; Gilbert) and increasingly in relation to social media research (Rieder; Gerlitz and Rieder), but the kind of analytical “dissections” we perform by selecting and designing metrics are less well understood. Metrics, however, equally need to be seen as epistemic devices that engage in breaking the practices sprawling on social media platforms apart and put them together again in various ways. The objective of the paper is to reflect on the affordances of different metrics in social media research and in particular in Twitter research. We draw on a previous experimental study on ‘mining one percent of Twitter’ (Gerlitz and Rieder) by expanding our initial reflections on the epistemic work and boundary making capacities of sampling to include the more subtle forms of carving implied by metrics.